THE INFLUENCE OF FINANCIAL ATTITUDE, FINANCIAL KNOWLEDGE, PARENTAL EDUCATION AND PARENTAL INCOME ON FINANCIAL MANAGEMENT BEHAVIOR IN PAMULANG UNIVERSITY POSTGRADUATE PROGRAM STUDENTS, EVEN SEMESTER Batch 2022/2023 - Masno Marjohan,; Erine Sulistiana,; Nafiisah Adhanurrizqi,; Nia Januari, (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This research aims to determine the influence of financial attitude, financial knowledge, parent education and parental income on financial management behavior in Pamulang University postgraduate program students for the even semester class of 2022/2023. This research used a purposive sampling technique which was carried out on 281 samples from 939 populations with the criteria of Pamulang University postgraduate program students class even semester 2022/2023. The methods used were questionnaires and interviews. The research results show that there is an influence of financial attitude, financial knowledge, parent education and parental income on financial management behavior of Pamulang University students, both simultaneously and partially. The implication is that students can make financial plans in order to practice more responsible financial behavior. Apart from that, students also need to realize that the ability to act and make financial decisions is very important for managing finances better.